How Interprofessional Collaboration and Transformational Leadership Affect Nurses’ Turnover Intention through Job Satisfaction - Peter Pratama; Supriyantoro Supriyantoro; Agusdini Saptaningsih (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Nursing turnover is problem for hospitals around the world, including at XYZ Hospital in Tangerang, Indonesia. Studies on the causes of turnover are required to reduce turnover effectively and efficiently. We aimed to study the effect of interprofessional collaboration and transformational leadership on turnover intention, with job satisfaction as intervening factor. This associative quantitative study gathered primary data obtained through survey on nurses at XYZ Hospital, Tangerang in April 2021, using Turnover Intention Scale-15, Interprofessional Collaboration Scale, Transformational Leadership Behavior Inventory, and McCloskey/Mueller Satisfaction Scale. Analysis was performed with Structural Equation Modeling (SEM) method. From a total of 95 subjects, we found that there was significant negative effect of Interprofessional Collaboration (β = -0.560, p = 0.004) and Transformational Leadership (β = ‑0.271, p = 0.031) on Turnover Intention through Job Satisfaction as intervening factor (β = -0.560, p = 0.004) and significant negative effect of Job Satisfaction on Turnover Intention (β = 0.808, p = 0.001). Also found was positive effect of Interprofessional Collaboration (β = 0.692, p <0.001) and Transformational Leadership (β = 0.335, p = 0.032) on Job Satisfaction. Therefore, promoting job satisfaction, interprofessional collaboration, and transformational leadership may be beneficial in reducing nursing turnover intention.